Simulation of the distribution symbols number in the binary delta - modulation signal - H. A. Gomtsyan (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The possibilities of using delta-modulation as analog-to-digital converter in the first stage in the new cascade coding structure for digital data processing systems are developed. Selecting the delta-modulation is motivated account of its simplicity, comparable to other types of analog-to-digital conversion, noise immunity, and most importantly, with a low probability of symbols bursts appearance. The latter property, as well as the using interleaver in the following stages of multi-coding can significantly improve the characteristics of digital data processing systems. The distribution of the symbols bursts for the various input signals and delta- modulation algorithms are obtained.